APPLICATION OF SELF DIRECTED LEARNING TO REDUCE MATHEMATICS ACADEMIC PROCRASTINATION - Siregar, Rahma; Nasution, Ja’far (ALGORITMA: Journal of Mathematics Education, 2024)
AbstractSelf Directed Learning is a learning process of self-will and self-control so that it can solve problems or tasks. This study examines the differences in academic procrastination in mathematics learning in groups that apply Self Directed Learning learning models and groups that use conventional learning models. This type of research is a quasi-experiment. The instrument of this research is an academic procrastination questionnaire given to 25 students in the control class and 26 students in the experimental class. This study's results indicate no significant difference in reducing mathematics academic procrastination in students who apply Self Directed Learning with students who apply conventional learning at SMP N 4 Padangsidimpuan. However, regarding the average value, there is a difference in reducing mathematics academic procrastination in students who apply Self Directed Learning with students who apply conventional learning at SMP N 4 Padangsidimpuan. So, classes with self-directed learning are better than classes with conventional learning. AbstrakSelf Directed Learning yaitu proses pembelajaran atas kemauan dari diri sendiri dan mengontrol diri sehingga dapat menyelesaikan permasalahan ataupun tugas. Penelitian ini bertujuan menguji perbedaan prokrastinasi akademik pada pembelajaran matematika pada kelompok yang menerapkan model pembelajaran Self Directed Learning dan kelompok yang menggunakan model pembelajaran konvensional. Jenis penelitian ini adalah quasi eksperimen. Instrumen penelitian ini adalah angket prokrastinasi akademik yang diberikan kepada 25 siswa di kelas kontrol dan 26 siswa di kelas eksperimen. Hasil penelitian ini menunjukkan tidak terdapat perbedan yang signifikan penurunan prokrastinasi akademik matematika pada siswa yang menerapkan Self Directed Learning dengan siswa yang menerapkan pembelajaran konvensional di SMP N 4 Padangsidimpuan. Tetapi ditinjau dari nilai rata-rata terdapat perbedaan penurunan prokrastinasi akademik matematika pada siswa yang menerapkan Self Directed Learning dengan siswa yang menerapkan pembelajaran konvensional di SMP N 4 Padangsidimpuan. Sehingga dapat disimpulkan kelas dengan pembelajaran self directed learning lebih baik daripada kelas dengan pembelajaran konvensional.